Insect Derived Lauric Acid as Promising Alternative Strategy to Antibiotics in the Antimicrobial Resistance Scenario - Borrelli, Luca; Varriale, Lorena; Dipineto, Ludovico; Pace, Antonino; Menna, Lucia F.; Fioretti, Alessandro (Frontiers in Microbiology, 2021)
Antibiotic misuse is greatly contributing to increase the development of antimicrobial resistance (AMR) in humans and animals. Natural and synthetic alternative strategies are being investigated in human and veterinary medicine, but still little attention is paid on the antimicrobial effects of the edible lipids, such as medium-chain fatty acids (MCFAs) and monoglycerides. Among MCFAs, lauric acid (LA) and its monoglyceride derivative, glycerol monolaurate (GML), exhibit the strongest antimicrobial activity. Coconut and palm kernel oils are considered as the main sources of LA. On the other hand, some edible insects (e.g. Hermetia illucens), are gaining interest as novel feed ingredients, due to their high amount of LA as well as numerous bioactive components, which provide many additional benefits to animal health. Although the beneficial effect of both MCFAs and LA is gradually being recognized, their high content within insects and, consequently, their possible role as antimicrobials, has not been well-reported. This mini review focuses on the anti-infective effects of the insect-derived MCFAs LA and its derivatives. We emphasize the potential of insect lipids, compared to the other vegetable sources, in the current global scenario where a sustainable and circular economy is highly requested. Finally, we critically discuss the use and the benefits of edible insects such as favorable options as feed and food in animal and human nutritional perspectives.